HUBUNGAN PERILAKU SEDENTARI DENGAN KEJADIAN OBESITAS PADA REMAJA DI SMP NEGERI 1 MOJOANYAR MOJOKERTO - Yulianti, Indra; Meilinawati, Elies; Ibnu, Faisal (WARTA BHAKTI HUSADA MULIA : Jurnal Kesehatan, 2018)
ABSTRACT Sedentary activities like playing computer games, watching television or another electronic media than walking, cycling or upand down movement on stair reduce energy output so positive balance happened where energy intake more than energy output. Body inclinely save the energy in fat form and then obesity happened. The goal of this research is to find out the the relation between sedentary behaviour with obesity incident on adolescent in SMP Negeri 1 Mojoanyar Mojokerto. Analytic research design with cross-sectional approach. The population is 435 people, the sample is 53 people with probability sampling technique (cluster random sampling). Measuring of sedentary behaviour with questionnaire and daily activity ta`ble, whereas measuring of obesity incident with CDC growth chart. A considerable part of respondens have sedentary behaviour but not in overweight is 26 people (49,0%), nearly half of respondens don’t have sedentary behaviour and not in overweight is 21 people (39,6%), few part of respondens have sedentary behaviour and in overweight is 3 person (5,7%) and no one responden who don’t have sedentary behaviour and not in overweight is 3 person (5,7%). Data analyzing with binary logistic regression test on SPSS 16.0. The research result show that there is the relation between sedentary behaviour with obesity incident p(0,000) < a (0,05). Sedentary behaviour or physical inactivity is a group of behaviour which do conciously and produce lowest energy output. Developing the better comprehension about sedentary behaviour is very important to prevent and reduce obesity on adolescent population. Reduce sedentary activities will able to control weight on adolescent